Leadership Transformation Policy: Perspectives of Private Schools in Indonesia - Agus Setyawanto; Bachtiar Hariyadi; Ahmad Hariyadi (STAI Miftahul Ula Nganjuk, 2024)
This study examines the perspectives of private school teachers in Indonesia regarding their preparedness for the role of school principal. The study focuses on the challenges faced by newly appointed principals, who typically lack formal certifications and instead rely on their teaching experience. Using a qualitative approach, the study employed interviews with teachers and an analysis of relevant documents. The findings reveal that many new principals feel inadequately prepared for their leadership responsibilities, particularly in areas such as curriculum management, human resources, school finance, stakeholder relations, and educational policy. The study highlights the importance of leadership training for teachers aspiring to principal positions. It recommends that prospective principals undergo comprehensive training programs, including certification, to ensure they are adequately equipped to manage schools effectively. This recommendation is crucial for the development of competent school leaders who can contribute to educational reforms in Indonesia.